Penjaminan Terhadap Hak Atas Desain Industri Sebagai Kekayaan Intelektual Ditinjau Berdasarkan UU Nomor 31 Tahun 2000 (Studi Kasus Pelanggaran Desain Industri Helm Bogo) - Daru Setyadharma Mardi Leksono; Fransiscus Ardiyan Bimantara; Yehezkiel Putra Pratama (CV. ITTC INDONESIA, 2025)
Industrial design is an important part of intellectual property that protects the visual appearance of a product, such as shapes, lines, or colors, which provides aesthetic value and distinguishes it from other products. The presence of Industrial Design Law 31 of 2000 is a tangible manifestation of the determination to provide protection for the right to industrial design in Indonesia. The protection of industrial design is inherent in the form of the Indonesian state which is constitutionally declared as a state of law which aims to encourage innovation, creativity, and provide legal certainty for designers and industry players. The industrial design registration process is carried out through the Directorate General of Intellectual Property (DJKI) and grants exclusive rights for a certain period of time. Dispute resolution can be done through litigation or through alternative dispute resolution.